Synthesis and Characterization of CN Thin Films Produced by DC-Pulsed Sputtering in an [latex]CH_3CH_2OH-N_2[/latex] Atmosphere - Marcos Crescencio González Domínguez; Pedro Guillermo Reyes Romero; Aarón Gómez Díaz; Horacio Martínez Valencia; Víctor Hugo Castrejón Sanchez (Advances in Science, Technology and Engineering Systems Journal, 2022)
This paper reports on the successful deposition of amorphous carbon nitride thin films (a-CNx). Samples were deposited using a DC-pulsed sputtering technique in CH3CH2OH-N2 atmosphere at constant pressure (1 Torr). Raman spectra were collected to investigate the bonding structure of the deposed thin films, while scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to study thin-film surface morphology. Plasma characterization was performed during the deposition process using optical emission spectroscopy (OES), and the influence of the deposition process parameters on the chemical fragmentation of species present in the plasma was determined. Raman results were typical for a-CNx films, and SEM analysis showed that carbon clusters deposited onto the Cu substrate form a non-homogeneous surface. The morphology observed by AFM indicated that the thin films grow as islands, which corroborate the generation of amorphous structures grown on the Cu surface. OES spectra verified the existence of CN radicals within the CH3CH2OH/N2 plasma during thin-film deposition.
Keywords: CNx; Sputtering; Raman; SEM; AFM; OES